A DOPS paranaense frente à Ação Integralista Brasileira durante o Estado Novo (1937-1945) : do "atentado contra o regime" à "associação nazi-integralista" - Athaides, Luciana Agostinho Pereira (2015)
This thesis aims to analyze the history of political repression to the remaining militants of the Brazilian Integralist Action in Paraná during the Estado Novo period, when the State was under the second government Manoel Ferreira Ribas as interventor (1937-1945). The research seeks to emphasize the modus operandi of the Bureau of Political and Social Order of Paraná front of the former integralists around two crucial contexts: the Integralist's Conspiracy (March / May 1938) and the Second World War (1939-1945). On the first, this research will examine the repression of state's political police against former AIB affiliated into subperiods: (1) after the start of the Estado Novo, when allied to the coup, the green shirts have become targets of surveillance and repression by Getúlio Vargas; (2) after the attempts of integralist armed uprising, when considered participants were harshly repressed and some of them tried and convicted by the Court of National Security. On the second context, this research analyzes the usual practices and imagery associations developed by DOPS to support suspicions, monitor and suppress the former integralists during the period of the Second World War, emphasizing the images of Nazi-integralist association, as well the of green-shirts as Axis 'fifth column'. Therefore, as a preamble, this monograph presents briefly the origins, the concept of political police and some relevant theoretical contributions to the study of that institution; then discusses the history of the emergence of DOPS (or Police Departments of Political and Social Order) in Brazil and Paraná, establishing dialogues with historiography. Still in an introduc?tory way, the text discusses the emergence and structuring of the call Paraná's Province of Brazilian Integralist Action, between 1934 and 1937, noting the construction, consolidation and suffered mishaps with local political powers of the party. Also will be placed in evidence the numbers, the social composition and the geographical range of integralist motion in the state, from another perspective of the sources, in dialogue with the existing historiography.